Wound bed assessment in patients at a tertiary hospital in Nigeria—a preliminary report (2016)
Introduction: Wound assessment is fundamental for the management of wounds. It is the foundation in the care plan and helps in determining the effectiveness of interventions. Wound assessment also assists in making appropriate decisions regarding the type of wound dressing to be applied. Detailed wound assessment takes into account all aspects of the patient’s well-being and not just the wounds the patient has. Objectives: The study assessed chronic wounds in the patients at a tertiary Nigerian hospital (University College Hospital, Ibadan) and utilized the information for preparing a standardized wound assessment format for health facilities in the subregion. Materials and Methods: The study was conducted at the University College Hospital, Ibadan, South West Nigeria. Patients with chronic wounds from various causes were treated prospectively in the hospital for over a month and had detailed assessment of their wounds performed. The data obtained were entered into a predesigned form, and this was subsequently analyzed using Statistical Package for the Social Sciences version 21 software. Results: Seventy-eight wounds were reviewed during the study period. The area of the wounds ranged from 1 to 1248 cm2 (median 24 cm2). The type of granulation tissue related to the wound type was not statistically significant. Assessment of the exudates of the wounds revealed that 44.9% of the wounds had seropurulent or purulent discharge, whereas 19.2% had serous discharge. Conclusion: Wound care management can be improved with appropriate wound assessments, which form the foundation in the care plan. Wound assessment will enhance objective measurement of the status of the wound and helps in choosing appropriate wound care dressing to promote wound healing.